BELIATN BAWO SAJIAN KEMASAN WISATA SANGGAR SENI SWALAS GUNAQ - Awensius, Awensius; Daryono, Daryono (Greget : Jurnal Kreativitas dan Studi Tari, 2024)
The treatment rituals in the Dayak Tonyoii and Benuaq communities are called Beliatn Bawo, a form of healing ceremony for non-medical diseases or illnesses (tenengkoah). The community's belief in the Beliatn Bawo ritual ceremony is a legacy of hereditary ancestral traditions whose implementation is led by an entrusted or elder, namely the pemeliatn. Apart from being a leader in healing rituals, as a medium of communication to ancestral spirits to gain magical-spiritual powers, and as a Beliatn Bawo dancer. This study uses a qualitative method, the report form uses analytical description by explaining the results of observations based on the actual situation. To strengthen this writing, several concepts or theories are used, namely the idea of form by Sumandiyo Hadi and Soedarsono, and a theory of tourism performances, the concept of tourism used by J. Maguet. Used an ethnochoreological approach to view dance as a tourist art product. Various stages have been carried out, namely data collection, observation, interviews, and literature study. The Beliatn Bawo dance was created by the Swalas Gunaq Art Studio. This dance is taken from the healing ritual tradition and then gets a creative artistic to become an art performance. In this way, the Swalas Gunaq Art Studio consciously develops its function as a tourism package to enrich the variety of arts, especially dance in West Kutai Regency, East Kalimantan. The tourist package Beliatn Bawo Dance includes elements of dance movements, music, offerings, props, make-up and clothing, mantras, and the pemeliatn Beliatn Bawo ritual dance.